Location, Location, Location: How Network Embeddedness Affects Project Success in Open Source Systems - Grewal, Rajdeep; Lilien, Gary L.; Mallapragada, Girish (Management Science, 2006)
The community-based model for software development in open source environments is becoming a viable alternative to traditional firm-based models. To better understand the workings of open source environments, we examine the effects of network embeddedness—or the nature of the relationship among projects and developers—on the success of open source projects. We find that considerable heterogeneity exists in the network embeddedness of open source projects and project managers. We use a visual representation of the affiliation network of projects and developers as well as a formal statistical analysis to demonstrate this heterogeneity and to investigate how these structures differ across projects and project managers. Our main results surround the effect of this differential network embeddedness on project success. We find that network embeddedness has strong and significant effects on both technical and commercial success, but that those effects are quite complex. We use latent class regression analysis to show that multiple regimes exist and that some of the effects of network embeddedness are positive under some regimes and negative under others. We use project age and number of page views to provide insights into the direction of the effect of network embeddedness on project success. Our findings show that different aspects of network embeddedness have powerful but subtle effects on project success and suggest that this is a rich environment for further study.